Uzbekistan : Climate Change and Agriculture Country Note - World Bank (Washington, DC, 2015)
This country note for Uzbekistan is part of a series of country briefs that summarize information relevant to climate change and agriculture for four pilot countries in the Europe and Central Asia (ECA) Region, with a particular focus on climate and crop projections, adaptation options, policy development and institutional involvement. The note series has been developed to provide a baseline of knowledge on climate change and agriculture for the pilot countries participating in the regional program on reducing vulnerability to climate change in ECA agricultural systems. For Uzbekistan, this note was shared with the Government and other agricultural sector stakeholders and used as an engagement tool for the National Awareness Raising and Consultation Workshop on reducing vulnerability to climate change in Uzbekistan s agricultural systems, held in Tashkent in May 2010. Feedback and comments on the note from this consultation process have been incorporated into this updated version in collaboration with the Uzbekistan Ministry of Agriculture and Water Resources (MAWR).